2022
DOI: 10.1007/s10661-022-09942-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful application of wastewater-based epidemiology in prediction and monitoring of the second wave of COVID-19 with fragmented sewerage systems–a case study of Jaipur (India)

Abstract: The present study tracked the city-wide dynamics of severe acute respiratory syndrome-corona virus 2 ribonucleic acids (SARS-CoV-2 RNA) in the wastewater from nine different wastewater treatment plants (WWTPs) in Jaipur during the second wave of COVID-19 out-break in India. A total of 164 samples were collected weekly between February 19th and June 8th, 2021. SARS-CoV-2 was detected in 47.2% (52/110) influent samples and 37% (20/54) effluent samples. The increasing percentage of positive influent samples corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Samples were then transferred to the Environmental Biotechnology Laboratory at Dr. B. Lal Institute of Biotechnology, Jaipur under cold chain transportation for pre-processing of wastewater and RNA extraction for sequencing as previously described. 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
“…Samples were then transferred to the Environmental Biotechnology Laboratory at Dr. B. Lal Institute of Biotechnology, Jaipur under cold chain transportation for pre-processing of wastewater and RNA extraction for sequencing as previously described. 22 , 23 …”
Section: Methodsmentioning
confidence: 99%
“…The RdRp gene labeled as CTR (orange) could not be detected at later time points, while the E gene labeled as CTE had higher detection than the N gene (CTN; Arora et al, 2021). Arora et al (2022) monitored the second and third waves of COVID-19 both qualitatively and quantitatively through community surveillance across Jaipur city in Rajasthan State. The study revealed increased detection sensitivity and supported WBE as an approach for early prediction of upcoming outbreaks, even in the cities like Jaipur, where the sewerage system is fragmented and not fully developed.…”
Section: Case Study: Wbe Surveillance In Indiamentioning
confidence: 99%
“…Previous studies have focused on the fate of viruses throughout WWTPs such as SARS‐CoV‐1 (Wang, Li, Guo, et al 2005; Wang, Li, Jin, et al 2005), pepper mild mottle virus (PMMoV), tobacco mosaic virus (TMV) (Tandukar et al, 2020a), Adenovirus (Hata et al, 2013), and so forth. Since the COVID‐19 pandemic, studies have been published on virus removal from various treatment processes, including individual wastewater treatment steps (Al‐Duroobi et al, 2023), advanced treatment (Polanco et al, 2023), and across the entire treatment plant (Arora et al, 2022; Sherchan et al, 2021; Foladori et al, 2022). These studies sometimes observed virus detection even after advanced treatment in the final effluent of wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%